IMPLEMENTASI MODEL PEMBELAJARAN VAK DAN PBL DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP MUHAMMADIYAH 33 JAKARTA - Nengsih, Retno (Jurnal Tunas Pendidikan, 2021)
The purpose of this study was to analyze the results of learning mathematics in the visual, auditory, and kinesthetic (vak) learning model and the problem-based learning (pbl) model for students of SMP Muhammadiyah 33 Jakarta. The research method used in this research is a quasi-experimental method. The sampling technique used was cluster sampling and simple random sampling. The instrument for collecting data was a test with 8 essays. The data analysis technique used is descriptive analysis technique and data requirements test. Test data requirements used are normality test and homogeneity test. In normality test, obtained sig. > α, means that data in the experimental and control class are normally distributed. In homogeneity test, obtained sig.> α, that is, both data have homogeneous variants. Furthermore, the hypothesis is tested using a free (independent) sample t-test. Based on the calculation, obtained sig. <α and tcount> ttable, so H0 is rejected and the mathematics learning outcomes of students who are given visual, auditory, and kinesthetic (vak) learning models are higher than learning outcomes who are given problem-based learning models. Thus, the VAK learning model is better than the PBL learning model for mathematics learning outcomes of SMP Muhammadiyah 33 Jakarta. Keywords: vak learning model, pbl learning model, efforts to improve learning outcomes.